Mobile augmented reality in learning chemistry subject: an evaluation of science exploration - Noor Hidayah Che Lah; Mohamad Syakir Zulpadhli Mat Senu; Nurul Farhana Jumaat; Danakorn Nincarean Eh Phon; Suhaizal Hashim; Nurul Nadwa Zulkifli (International Journal of Evaluation and Research in Education (IJERE), 2024)
Various technologies have been used in making teaching and learning sessions more effective, fun, and enjoyable. One of the ways to make teaching and learning interactive is by emphasizing the use of mobile augmented reality (MAR). Thus, this study has proposed using MAR for a chemistry subject, namely science exploration (SCIENEX). This study adopted design and development research (DDR) by employing the analysis, design, development, implementation, and evaluation (ADDIE) model. The phases involved in DDR are ADDIE. SCIENEX was evaluated based on its validity, usability, and effectiveness. Five experts validated SCIENEX after it had been completely developed. The samples for usability testing and effectiveness of SCIENEX were 30 secondary school students who were studying chemistry. The results of the evaluation of the experts’ validation revealed that SCIENEX is a valid and appropriate MAR application for the learning of topics in chemistry. The result also revealed that the majority of students strongly agreed that SCIENEX is appropriate for the usage of MAR in learning chemistry, as it is fun, easy to use, and helps students to understand their learning. Interestingly, SCIENEX could increase students’ performance in their learning (t=21.754; p=0.000). Thus, it can be concluded that SCIENEX is valid, can be used for learning chemistry, and can help students in their learning. The limitations of this study and future suggestions for research are also discussed.